Effects of grafting and long-chain branching structures on rheological behavior, crystallization properties, foaming performance, and mechanical properties of polyamide 6 - Cao Lushuai; Jiang Tuanhui; Liu Bujin; Li Ming; Zhang Di; Gong Wei; He Li (e-Polymers, 2022)
Polyamide 6 (PA6) was modified with ethylene maleic anhydride syndiotactic copolymer resin (ZeMac), and triglycidyl isocyanurate (TGIC) as modifiers to prepare a grafting structure and a long-chain branching structure, respectively. The effects of two modifiers on the rheological behavior, crystallization properties, foaming performance, and mechanical properties of PA6 were systematically studied by rotating rheometry, differential scanning calorimetry and scanning electron microscopy. The results showed that there were differences in crystallization properties between the two modification methods, but they significantly improved the rheological, foaming performance, and mechanical properties of PA6. In particular, PA6 with long-chain branching structure through TGIC modification showed better performance in various physicochemical characterizations. The introduction of ZeMac reduced the average diameter of bubbles in pure PA6 from 146.32 to 88.12 µm, and the density of bubbles increased from 1.69 × 105 to 5.35 × 105 cells·cm−3. The introduction of TGIC reduced the average diameter of bubbles in pure PA6 from 146.32 to 64.36 µm, and the density of bubbles increased to 1.31 × 106 cells·cm−3. Moreover, the mechanical properties of both nonfoamed and foamed samples were improved after modification.